(untitled) (Marketing Journal, 2025)
This article analyzes the importance of pricing in companyʼs future profit in management accounting. Because it makes a vital contribution to profit maximization – the overriding aim of most businesses. Businesses make profits by selling goods and services at a price higher than their cost. The amount that they are able to sell will often be determined by the price charged for the goods and services.